Bankruptcy Boedel Execution Practices in Indonesia (Faculty of Law, Universitas Negeri Semarang, 2020)
The ASEAN economic community is one of the pillars of the agreement to form ASEAN. As the integrated economic identity of Southeast Asia, MEA aims to create a single market and production base marked by the free flow of goods, services and investment. A bankruptcy issue crosses national borders arises, when debtors in Indonesia have bankrupt assets abroad. Where the bankruptcy execution process is hampered by existing rules in the country itself, especially in ASEAN, one of the international organizations in the regional level which is one of Indonesia's members, does not yet have regulations that bind its members to the problem of bankruptcy boedel. 1967 UN model law